1998
DOI: 10.1136/hrt.80.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Five minute recordings of heart rate variability for population studies: repeatability and age-sex characteristics

Abstract: Objective-To evaluate the stability of short recordings of heart rate variability (HRV) with time, and the association of HRV with age and sex. Design-Five minute Holter recordings were made twice over a two month interval (tracking study). In addition, HRV was measured in a cross sectional study. Setting-Residents of 11 Israeli kibbutzim were examined in their settlements. Subjects-32 men and 38 women (aged 31-67) participated in the tracking study and 294 (aged 35-65) were involved in the cross sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
155
5
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(203 citation statements)
references
References 32 publications
31
155
5
5
Order By: Relevance
“…Other reports on short-term recordings of HRV showed widely dispersed mean values in the range of 6.2-10.4, 4.7-10.0 and 4.9-10.0 for lnTP, lnLF and lnHF, respectively. 8,10,24,[28][29][30][31] The mean values in the present study were all within these ranges. Reproducibility of the HRV measurement was not examined in the present study by repeating the recordings within a relatively short interval.…”
Section: Discussionsupporting
confidence: 62%
“…Other reports on short-term recordings of HRV showed widely dispersed mean values in the range of 6.2-10.4, 4.7-10.0 and 4.9-10.0 for lnTP, lnLF and lnHF, respectively. 8,10,24,[28][29][30][31] The mean values in the present study were all within these ranges. Reproducibility of the HRV measurement was not examined in the present study by repeating the recordings within a relatively short interval.…”
Section: Discussionsupporting
confidence: 62%
“…Larger sex differences in sympathetic parameters, such as the very low and low frequency power, have been previously reported [6], perhaps relating to greater sympathetic activity in men compared to women, in whom muscarinic regulation of HRV may be more important [7], although this hypothesis is not consistent with previous data in young and middle-aged adults [8].…”
contrasting
confidence: 61%
“…In contrast, other studies showed a decline in HRV with age [2,6], although those studies were mainly carried out in older subjects, whilst our investigation included healthy young subjects.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Standing comprises an orthostatic challenge, the autonomic response to which is typified by a reproducible decreased HF and increased LF contribution to total spectral power [26]. The use of controlled breathing typically increases the vagal contribution to SA node control [27]. CHF patients with sympathetic hyperactivity tend to show blunted decreases in vagal indices (HF, HFnu) and increases in indices (LFnu) of sympathetic activation [26].…”
Section: Autonomic Response To Standing and Controlled Breathingmentioning
confidence: 99%